A CHANGE DETECTION ANALYSIS IN THE IZMIR BIRD PARADISE: INTEGRATION OF REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEM - Dogru, Ahmet Ozgur; Balcik, Filiz Bektas; Sanli, Fusun Balik; Goksel, Cigdem; Ulugtekin, Necla (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2009)
Wetlands are one of the most important natural areas of the world, since they provide habitats to various kinds of animals and plants, some of which are endemic and perform vital ecosystem services, including carbon sequestration, water quality protection, anti flood mitigation. Unfortunately, wetlands are destroyed by human-induced effects such as urbanization and pollution. Turkey has several wetlands, and nine of these areas are defined as A type-wetlands according to the RAM-SAR agreement, which was signed by Turkey in 1994. The Izmir Bird Paradise is one of the most valuable wetlands. However, this area has been threatened by the drying out of marshes, unplanned urbanization, agricultural facilities, and water pollution for years, A significant ecological disaster had been experienced leading up to the year 2002, when the area was selected as a first-degree nature protection zone. The aim of this study is to determine the dimensions of the continuing human-induced ecological disaster at the Izmir Bird Paradise. For this purpose, integration and classification techniques are used to measure the changes in this Bird Paradise by using Landsat data acquired in 2000, 2003, and 2006. The results obtained in this study clearly show that urbanization seriously affected the study area during the 6-year period. During this period, the urban areas have been expanded from 1626.66 ha to 3439.35 ha, and the wetland areas have been reduced from 701.55 ha to 595.63 ha. A considerable amount of area loss has occurred in the agricultural lands. The results show that the study area is still under the threat of human-induced damage.
Keywords: Ecological disaster; wetlands; remote sensing; GIS; CLASSIFICATION; LAND; Environmental Sciences & Ecology